2009
DOI: 10.1007/978-3-642-00302-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Something Old, Something New: Plant Innate Immunity and Autophagy

Abstract: Autophagy performs a variety of established functions during plant growth and development. Recently, autophagy has been further implicated in the regulation of programmed cell death induced during the plant innate immune response. In this chapter we describe specific mechanisms through which autophagy may contribute to a successful defense against pathogen invasion. Accumulating evidence shows that the plant immune system utilizes the chloroplasts as primary sites for the regulation of cell death programs. Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 87 publications
0
13
0
1
Order By: Relevance
“…Oxidative stress observed during S. sclerotiorum infection is likely responsible for damage to the chloroplast and a reduction in photosynthetic activity [56, 57]. In Ss-treated plants, the observed upregulation of CLH1 is likely due to chloroplast damage leading to the release of chlorophylls from thylakoid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress observed during S. sclerotiorum infection is likely responsible for damage to the chloroplast and a reduction in photosynthetic activity [56, 57]. In Ss-treated plants, the observed upregulation of CLH1 is likely due to chloroplast damage leading to the release of chlorophylls from thylakoid membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the ATG13 homologues have been retained in plants but have been lost in animals. Further studies are needed to determine whether ATG13 in plants performs a similar function (Seay et al, 2009). …”
Section: Initiationmentioning
confidence: 99%
“…The most striking characteristics of HR are rapid cell death at the infection site and the activation of a series of defense responses (McDowell and Dangl 2000). For instance, studies have shown that HR PCD is the most important and obvious response to pathogen invasions because it limits pathogens at the infection site by killing cells in the susceptible regions in order to protect the plant (Liu et al 2005, Seay et al 2009). Autophagy-deficient mutant plants fail to limit the spread of cell death and lose the ability to resist infection Dinesh-Kumar 2008, Yoshimoto et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A typical response is rapid cell death in plant leaves at the infection site, which is known as the hypersensitive response programmed cell death (HR PCD) (Liu et al 2005). The HR PCD is triggered upon infection by an avirulent pathogen to limit both the spread of cell death and the pathogen, and it protects healthy adjacent cells from pathogen attack (Lam 2004, Seay et al 2009). Autophagy is induced in the plant defense response against pathogens, and it leads to a negative regulation of PCD (Liu et al 2005, Seay et al 2006.…”
Section: Introductionmentioning
confidence: 99%